The Effect of Job Insecurity and Perceived Organizational Inclusion on Outsourcing Employee Performance - Boyas, Jeziano Rizkita (GREENOMIKA, 2024)
This study aims to examine the influence of job insecurity and perceived organizational inclusion on the performance of outsourced employees at PT Karya Utama Nusindo (KUN). A quantitative approach was used with a survey method involving 83 respondents from five partners of PT KUN. Job insecurity was measured using 5 indicator items, while Perceived Organizational Inclusion used 6 indicator items. Employee performance uses 6 indicator items. The results showed that job insecurity has a positive and significant effect on employee performance, meaning that job uncertainty actually motivates employees to work better. Meanwhile, perceived organizational inclusion also has a significant positive effect, indicating that an inclusive work environment encourages optimal performance. This research provides insight for companies to leverage these factors in improving outsourced employee performance through a strategic approach that manages job insecurity productively and encourages organizational inclusiveness.